"Do the Write Thing": Writing Schizophrenia in Singapore. (2nd January 2021) - Holden, Philip
Abstract: This essay examines two recent memoirs of schizophrenia in Singapore: Chan Lishan's A Philosopher's Madness and Danielle Lim's The Sound of Sch . The narratives, through the memoir form, question voice, agency, and self-making in a society in which colonial governing rationalities have now transformed into national and neoliberal ones.